Avoiding innocence: unsettling white guilt. Issue 2 (September 2018) - Zanussi, Darren
Abstract : In this anecdotal article, I employ Eva Mackey's concept of settler uncertainty to analyse my place in settler colonialism. I grew up in the quintessential Canadian setting of Parry Sound, Ontario – a town steeped in anti-Indigenous racism as much as nationalistic imagery. However, majoring in Canadian studies at Carleton University forced me to grapple with the colonial and racist nature of my upbringing. This self-reflexive piece critically examines my motivations for entering academia through formative stories from my childhood and reflections on my scholarly pursuits, exploring the influence of guilt on my so-called transformation. This article was originally written during my political science undergraduate degree at York University. Rather than updating it I have added another level of reflection critically analysing the previous work. I outline my previous adherence to colonial structures, my internal struggle to leave them behind, and ongoing reflections concerning settler decolonisation within the academy.